2015
DOI: 10.1177/070674371506000306
|View full text |Cite
|
Sign up to set email alerts
|

The National Trajectory Project of Individuals Found Not Criminally Responsible on Account of Mental Disorder in Canada. Part 3: Trajectories and Outcomes through the Forensic System

Abstract: Objective: To examine the processing and Review Board (RB) disposition outcomes of people found not criminally responsible on account of mental disorder (NCRMD) across the 3 most populous provinces in Canada. Although the Criminal Code is federally legislated, criminal justice is administered by provinces and territories. It follows that a person with mental illness who comes into conflict with the law and subsequently comes under the management of a legally mandated RB may experience different trajectories ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…To facilitate interpretation, the reference category is always the more restrictive disposition: positive coefficients indicate a greater likelihood of a less restrictive decision. As observed in our previous work (Crocker, Charette, et al, in press), there is a difference across provinces in review board dispositions. Ontario and BC review boards are less likely to grant CDs than QC.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…To facilitate interpretation, the reference category is always the more restrictive disposition: positive coefficients indicate a greater likelihood of a less restrictive decision. As observed in our previous work (Crocker, Charette, et al, in press), there is a difference across provinces in review board dispositions. Ontario and BC review boards are less likely to grant CDs than QC.…”
Section: Resultssupporting
confidence: 80%
“…The present study builds on our previous research (Crocker et al, ; Crocker, Charette, et al, in press) to further examine how dynamic and static variables predict disposition decisions for NCRMD individuals across the three largest provinces in Canada.…”
Section: The Present Studymentioning
confidence: 97%
See 1 more Smart Citation
“…The NTP (https://ntp-ptn.org, ) was an archival, longitudinal study examining a cohort of Canadian individuals found NCRMD in British Columbia (BC), Ontario (ON), and Québec (QC). The full methodology is described in detail by Crocker and colleagues (Crocker et al, ; see also Charette et al, ; Crocker et al, ; Crocker et al, 2015a–c; Nicholls et al, ; Salem et al, ; Wilson et al, ). Details relevant to the current analyses are presented here.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the 3‐year duration of the observation period of this study might have had an impact on the lack of variability in the trajectories of this sample. Longer follow‐up periods would allow us to see more variation over time in placement patterns, particularly for individuals who committed a severe index offense, for whom duration under Review Board is longer (Crocker et al, ) and for whom housing resources may be particularly difficult to access.…”
Section: Discussionmentioning
confidence: 99%